Dermoscopy and non melanocytic hyperpigmentation of the skin. - Bonifazi, E.; Ciampo, L.; Milano, A. (European Journal of Pediatric Dermatology, 2005)
Non melanocytic skin hyperpigmentation of 38 subjects, 19 with hyperpigmented nevus, 9 with neurofibromatosis, 7 with nevus spilus and 3 with Becker's nevus were studied. The hyperpigmented lesions were first clinically classified and then dermoscopically investigated at 10x magnification. Dermoscopic findings are not able in differentiating hyperpigmented nevus from café-au-lait spots. A net pattern is not always expression of a melanocytic proliferation, being regularly present in Becker's nevus and, exceptionally, in hyperpigmented nevus, café-au-lait spot and even in hyperpigmented normal skin.